Assessment of Toll User Satisfaction in East Java Using Simple Additive Weighting (SAW) - Utomo, Pradityo; Fatmawati, Laily; Rochidajah, Rochidajah; Amadi, Dwi Nor (Journal of Information Systems and Informatics, 2022)
Toll roads are one of the transportation media that can be used to facilitate travel. But only vehicles with at least four wheels can enter the toll road area. Toll roads have several service facilities including transaction services, traffic services, construction services, information services, PJR (Highway Patrol) services, and rest area services. Of these services have service attributes. Where the attributes of the services of the service type can be used as research alternative data. The assessment criteria are the class 1 vehicle satisfaction index and the non-group 1 vehicle index. Then from these criteria and alternatives, it can be done to fill in the value data from the survey results on 95 toll road users from group 1, and 49 toll road users from non-group 1. From the data from the survey results, the data is then indexed. Index data can be used as decision-making value data. With criteria data, alternative data, and value data can be created a decision support system (DSS). The development of DSS can be used for satisfaction analysis which can further provide consideration for the government or toll road managers regarding the types of services that need to be improved. This analysis system uses the Simple Additive Weighting (SAW) method. From the results of the study, recommendations were obtained for each attribute of the type of service that must be prioritized for its implementation.